2018
DOI: 10.28978/nesciences.379327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Work Zone Safety

Abstract: The increase in number of vehicles and deterioration of the existing facilities necessitates the need to improve the existing roadways and to build additional highways hence creating more work zones in cities around the globe. Two work zones one on a rural road and one on an urban road were studied to identify potential hazards in work zone and determine the most dangerous area of the work zone using risk concentration level. Confusing signs, use of dangerous devices for road closure, missing buffer, missing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Specifically, 55.2% of road users and 60.2% of civil engineers said that the transition area was the area with the highest risk probability of causing a crash in the WZ, followed by the advance warning area, 18.4% of road users, and 21.4% of civil engineers. This agrees with studies conducted by Jin and Saito (2009) and Khalil and Samir (2018) that stated the most crash-prone area location is the transition area [ 17 , 18 ]. In addition, approximately 92% of both groups reported that they obey WZ ahead signs by reducing their vehicle speed.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, 55.2% of road users and 60.2% of civil engineers said that the transition area was the area with the highest risk probability of causing a crash in the WZ, followed by the advance warning area, 18.4% of road users, and 21.4% of civil engineers. This agrees with studies conducted by Jin and Saito (2009) and Khalil and Samir (2018) that stated the most crash-prone area location is the transition area [ 17 , 18 ]. In addition, approximately 92% of both groups reported that they obey WZ ahead signs by reducing their vehicle speed.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, most respondents thought that the presence of better and good condition TCD on WZ sites would definitely improve the safety of the WZs. That agrees with studies by Garber and Woo (1990), Jin and Saito (2009), Khalil and Samir (2018), Li and Bai (2008), Osman et al (2018), and Ullman et al (2008), which emphasized that the presence of a good condition of the TCD is effective and has a positive impact on work zone safety [ 9 , 17 , 18 , 21 , 24 , 31 ]. In terms of using developed technologies, it seems that deploying smart technologies in smartphone applications or within vehicles would affect and improve the health and safety of road work zones.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations